(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
A protocol was developed for in vitro clonal propagation of Rauvolfia serpentina through direct regeneration from shoot tip explants. Multiple shoots (eight shoots per explant) induction were obtained on MS medium supplemented with 4.0 mg/l BAP and 0.5 mg/l NAA within 10-15 days. The elongated shoots rooted well in half strength MS medium with 0.5 mg/l NAA. The in vitro raised plantlets were acclimatized in glass house and successfully transplanted to field condition with 80 % survival. The results indicated that large scale commercial micropropagation of Rauvolfia serpentina is technically feasible. Bangladesh J. Sci. Ind. Res. 42(1), 37-44, 2007